THE ROLE OF INTERNAL COMMUNICATION IN BUILDING A POSITIVE CORPORATE CULTURE - Fajar Rahmat Aziz; Kowiyanto Kowiyanto; Hasdiana Hasdiana (INJOSEDU: International Journal of Social and Education, 2025)
In a dynamic business environment, maintaining a positive corporate culture is key to long-term success. The role of internal communication in the process of establishing and maintaining a positive organisational culture has been widely debated, but there is no clear consensus on the most effective communication strategies and techniques. The method used in this research uses literature research method. The findings of this study indicate that effective internal communication plays an important role in the formation and maintenance of a positive corporate culture. Key findings include the importance of transparency, openness, and two-way dialogue between management and employees. In addition, the use of innovative communication technologies was found to increase employee engagement and facilitate the establishment of a collaborative and supportive work community.